STORYTELLING QUR’ANY: BENTUK NARASI KISAH DALAM AL-QUR’AN - Zainuddin Zuhri (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2026)
The storytelling method in the Qur'an has been a subject of interest and significance for scholars and readers alike. However, many laypeople still lack a deep understanding of how the stories in the Qur'an are narrated. Previous research has predominantly focused on the lessons derived from these stories, while there has been limited exploration of the narrative structure employed in the Qur'anic narratives. This study aims to elucidate the narrative techniques used in the storytelling of Qur'anic verses. The research findings indicate that the narrative style in the Qur'an often begins with a brief summary in a few words, which is then simplified to clarify the core of the story. The significance of these stories is sometimes expressed through shifts in narrative levels, moving between higher and lower levels of argumentation and refutation. Additionally, the storytelling in the Qur'an sometimes commences directly from the climax of the story, without a prologue, thus engaging the reader's imagination directly. Within these narratives, religious admonitions are often inserted, enriching the understanding of the moral messages embedded in the stories. This study contributes to a deeper understanding of the narrative techniques employed in the storytelling of the Qur'an, shedding light on its unique and profound storytelling tradition.